2017
DOI: 10.1021/acs.analchem.7b01301
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Aquatic Toxicity through Chromatographic Systems

Abstract: Environmental risk assessment requires information about the toxicity of the growing number of chemical products coming from different origins that can contaminate water and become toxicants to aquatic species or other living beings via the trophic chain. Direct toxicity measurements using sensitive aquatic species can be carried out but they may become expensive and ethically questionable. Literature refers to the use of chromatographic measurements that correlate to the toxic effect of a compound over a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Relative to other data collection methods, QSARs are expeditious and have the prospective to include diverse entities that are reliant on the model domain. Additionally, the appraised facts, for example, by QSARs, are expected to upsurge in significance as authorizations such as the European Chemicals Agency promote the reduced use of animal testing. , In this study, the QSAR method was explored to investigate the formation plausibility of the synthesized chemicals in Table and predict the effect of different functional groups attached to the main structure for their toxicity hazard and protein binding (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Relative to other data collection methods, QSARs are expeditious and have the prospective to include diverse entities that are reliant on the model domain. Additionally, the appraised facts, for example, by QSARs, are expected to upsurge in significance as authorizations such as the European Chemicals Agency promote the reduced use of animal testing. , In this study, the QSAR method was explored to investigate the formation plausibility of the synthesized chemicals in Table and predict the effect of different functional groups attached to the main structure for their toxicity hazard and protein binding (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The addition of the cosurfactant produced important differences between the mobility values obtained with or without it, although the reason for these differences has not been systematically studied. Taking into account that the retention factor of a substance in a given system is often used to estimate other of its properties, such as logPo/w [8][9][10][11] or biopartitioning parameters [20][21][22][23][24], it is very important to ensure it is determined correctly.…”
Section: Introductionmentioning
confidence: 99%
“…In concrete and according to both the distance and the clustering criteria, the biological systems that probably will be best emulated by the lecithin systems are toxicity to tadpoles and skin partition. Our group of research has recently reported a method using MEKC to surrogate the toxicity to tadpoles [13] and other species [23] and a method using RPLC to surrogate skin partition [24]. The RPLC method uses a C18 stationary phase and 10 mM phosphate buffer (pH 7) :…”
Section: Similarity Of the Lecithin-based Systems And The Biological Systemsmentioning
confidence: 99%